The evolution of the winter paralympic games and sports - Giovanis, V.; Margari, E. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: The aim of this research was to record and the evolution of the winter paralympic games and sports since 1976 until 2010. The history of the Winter Paralympic Games is relatively recent compared to that one of the Olympic Games. The first Games were held in 1976 in Ornskoldsvik, Sweden and the most recent, 38 years later in 2014, in Sochi, Russia. This article will examine the Winter Paralympic Games up until the ones in 2010 in Vancouver, Canada. During these years, there have been many changes in relation to the Games itself, the governing body of the Paralympic Movement, the sports' facilities, the sports involved and sports' categories. The motivation for writing this paper was the need to record and gather all of these items in one paper. Gathering information for the Winter Paralympic Games will be an important theoretical background. This information will create a database for the structure of the governing body of the Paralympic Games, for the organization of the Games [Local Organizing Committee (LOC), venues and equipment], for the evolution of the Winter Paralympic Sports and the categories of the athletes, as well as the evolution of the athletes' and sports' participation.